(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2020)
Sariakandi fish pass is unique connecting Jamuna and Bangali rivers through an engineered channel. A study was conducted on the fish pass aiming to improve fish diversity in north-west Bangladesh. Sampling at the fish pass, market census, interviewing the locals and focus group discussion were done to collect data from the study area. A total of 69 fish species under 9 orders and 26 families were recorded. Cypriniformes (22 species) was the most dominant order followed by Siluriformes (21 species), Perciformes (13 species), Clupeiformes (4 species), Synbranchiformes (4 species), Osteoglossiformes (2 species), Mugiliformes (1 species), Anguilliformes (1 species) and Tetraodontiformes (1 species). In total 30 threatened species in Bangladesh and globally recognized 9 species were recorded. This fish pass is not working during the dry or winter seasons but helps in the diversified fish migration diversity of Bengali and Jamuna river system during the flood time of Bangladesh. The present study recommends establishing effective fish passages in flood protection structures or dams in Bangladesh to retain the connectivity of fish migration routes and the improving of fish diversity. J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(2): 53-62